Pengaruh Efikasi Keuangan dan Kemampuan Akademik Terhadap Pengelolaan Keuangan Mahasiswa Prodi Pendidikan Ekonomi Universitas Sebelas Maret Angkatan 2016-2019 - Ari Sulistyowati; Mintasih Indriayu; Sudarno Sudarno (Journal on Education, 2023)
The background of this research involves the obstacle faced by students after college graduation that drive their businesses into failure. This obstacle is capital which could be obtained during college with good financial management Therefore it is formulated how financial efficacy and academic ability influenced student financial management The goal of this study is to ascertain the effect of financial efficacy and academic ability on students’ financial management. This research used the quantitative method in which the data was collected through questionnaires with the total of 176 student respondents. Data analysis was performed with multiple linear regression analysis. After being processed, the data results in information that indicates that financial efficacy and academic ability do have a positive and significant effect on student financial management behavior. Academic ability was found to have a higher impact on financial management than financial efficacy. Therefore, to improve student financial management, it is necessary to improve their academic abilities alongside their financial efficacy.